1998
DOI: 10.1159/000023289
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Leptin in Cafeteria-Diet-Overfed Rats

Abstract: In a group of 15 male Wistar rats overfed with cafeteria foods (delivering a mean fat percentage of 60%) during 5 months from the age of 8 weeks and in a control group of 15 rats fed with a standard chow for the same period, serum leptin, insulin and corticosterone were measured by RIA and body composition was determined by dual-energy X-ray absorptiometry. Significantly higher fasting serum concentrations of leptin, insulin and corticosterone were found in the cafeteria-diet group. Fasting leptin concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the present study, only 4 weeks on a hyperlipidic diet, both continuously and alternated with a chow diet, caused an enhancement in adiposity that was accompanied by an increase in serum leptin concentration, which shows that short periods of hyperlipidic diets can promote obesity. In previous studies, several obese animal models have also developed elevated circulating leptin levels [15,40]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, only 4 weeks on a hyperlipidic diet, both continuously and alternated with a chow diet, caused an enhancement in adiposity that was accompanied by an increase in serum leptin concentration, which shows that short periods of hyperlipidic diets can promote obesity. In previous studies, several obese animal models have also developed elevated circulating leptin levels [15,40]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that rats fed a high-fat diet had an increased fat mass percentage even when the energy intake was not elevated [15,16]. Likewise, we previously demonstrated that the continuous intake of a hyperlipidic palatable diet and the alternation of a high-fat intake with periods of chow intake for 8 weeks caused obesity and affected the lipid metabolism of rats in a similar way, although the energy intake remained unchanged (KJ) [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of reports showed that serum leptin levels did not change significantly during the estrus cycle in rats [28, 29, 30]. On the other hand, Bennet et al [31]reported that serum leptin levels tended to increase during proestrus in rats.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of excessive calorie intake for example, leptin resistance has been proposed to provoke diet-induced obesity in animals and humans (3). Most studies have shown that high-fat diets can both increase the ob gene expression in adipose tissue and augment circulating leptin levels (4)(5)(6). However, controversy exists since high-fat diets also have been associated with a suppression of plasma leptin levels (7).…”
mentioning
confidence: 99%